A chronology of early medieval Western Europe - Venning, Timothy, author.
1 online resource (vi, 606 pages)
Keywords: "A Chronology of Early Medieval Western Europe uses a wide range of both primary and secondary sources to chart the history of Britain and Western Europe, with reference to the Celtic world, Scandinavia, the Mediterranean and North America. Extending from the middle of the fifth century to the Norman Conquest in 1066, the book is divided into five chronologies that present the day-to-day developments of events such as the fall of Rome, the Viking invasion and the military campaigns of King Alfred, as well as charting the cult of the mysterious 'King Arthur'. Timothy Venning's accompanying introduction also provides a discussion of the different types of sources used and the development of sources and records throughout these centuries. Tying together the political, cultural and social elements of early medieval Western Europe, this chronology is both detailed and highly accessible, allowing students to trace this complex period and providing them with the perfect reference work for their studies. "--Provided by publisher.